Penguatan Dukungan Psikologis dan Kebugaran Ibu Hamil Melalui Prenatal Happy Yoga di Era Digital - Qatrunnada Naqiyyah Khusmitha; Vina Firmanty Mustofa; Evy Wulandari; Nidya Comdeca Nurvitriana; Devi Maya Arista; Karunia Wijayanti; Nastiti Aryudaningrum; Meylani Zakaria (Center for Community Service and Science and Technology Marketing - The Institute for Research and Community Service Universitas Negeri Surabaya, 2025)
Pregnancy is a time when a woman's body and emotions go through big changes, which can make her feel more stressed and worried. Even though staying active is good for her health, many pregnant women don't take part in physical activities. This shows that there's a strong need for easy-to-reach, fun, and non-drug treatments that help moms feel better. A community program was created to help pregnant women learn more about their health, get emotional support, and stay fit through a digital yoga program called Prenatal Happy Yoga. The program included 27 pregnant women who were grouped by the trimesters. It had three parts: first, getting ready and checking their health, then having talks about mental health and doing yoga exercises that match each stage of pregnancy, all led by trained instructors. Lastly, they collected feedback from the participants. The program was based on the Theory of Planned Behavior, which looks at how attitudes, what others think, and how easy it is to do something influence healthy choices. The results showed that the women were very involved, loved the sharing sessions, and enjoyed the 50-minute yoga classes. After the program, they had a better understanding of how important it is to keep both their body and mind in balance during pregnancy. Even though there were some small technical problems, the program ran smoothly and shows promise for being used more widely as a digital health and prevention tool for pregnant women.